Analisis RASCH untuk menganalisis instrumen penilaian kecemasan pada ibu nifas - Gumilang, Lani; Linasari, Desy (ACTA Medical Health Sciences, 2024)
Globally, an estimated 20% of women who give birth experience postpartum anxiety. Women, after childbirth, require both physical and psychological adaptation. If not treated immediately, postpartum mothers can experience different levels of anxiety. Anxiety in postpartum mothers can harm both mother and baby. Therefore, health workers need to detect anxiety immediately. This assessment (Postpartum Specific Anxiety Scale), or PSAS, helps health workers assess anxiety in postpartum mothers starting from the beginning of the puerperium. However, this measuring instrument needs to be evaluated to assess its use. A Rasch analysis is needed to accurately picture postpartum maternal anxiety. It is considered to have the ability to enhance the accuracy of statistical analysis results and increase measurement precision. This research aims to analyze the postpartum maternal anxiety assessment instrument using Rasch analysis. This study used a descriptive method with a cross-sectional research design involving 36 spontaneous postpartum mothers. The Postpartum Specific Anxiety Scale (PSAS) is the instrument used in this study. According to the results of analysis using the Winsteps program, it is known that there are 34 out of 51 items that meet the item-model accuracy index, with an alpha coefficient of 0.94. The instrument’s separation item index has a value of 3.06. The unexplained variance value does not exceed 15%, so this instrument is ideal for use. Overall, it can be concluded that the anxiety assessment scale for postpartum mothers, namely PSAS, has good psychometric properties for assessment and research. DOI : 10.35990/amhs.v2n3.p138-147 REFERENCES Ministry of Health. Indonesian Basic Health Research Result Report. 2013. Jakarta: Ministry of Health. Oktafia R, Berliyanti AE, Indriastuti AN, Rahmayanti R. Infant Temperament with Anxiety in Postpartum Mothers in Primary Health Care Sleman, Indonesia. Bali Medical Journal. 2023;12(1):451-455. doi: 10.15562/bmj.v12i1.36993. World Health Organization. Maternal Mortality. Geneva: Department of Reproductive Health and Research, WHO; 2023. Zappas PM, Becker K, Moss WB. Postpartum Anxiety. The Journal for Nurse Practitioners. 2020:1-5. https://doi.org/10.1016/j.nurpra.2020.08.017. Rees S, Channon S, Waters SC. The Impact of Maternal Prenatal and Postnatal Anxiety on Children's Emotional Problems: A Systematic Review. European Child & Adolescent Psychiatry. 2018;28:257-280. https://doi.org/10.1007/s00787-018-1173-5. Nagel M, Emily et al. Maternal Psychological Distress and Lactation and Breastfeeding Outcome: A Narrative Review. Department of Health and Human Services-USA. 2022;44(2):215-227. doi: 10.1016/j.clinthera.2021.11.007. Fernandez-Vaz C, Gonzalez-Sanz JD. Cortisol, Maternal Stress, and Breastfeeding Rate at Hospital Discharge: A Systematic Review. Breastfeed Med. 2022;12:984-993. https://doi.org/10.1089/bfm.2022.0165. Carrega J, Lee SY, Clark P, Cranford J, Lloyd S. Impact of the Quality of Postpartum Sleep and Its Health Determinants on Human Milk Volume. MCN Am J Matern Child Nurs. 2020;45(5):289-295. doi:10.1097/NMC.0000000000000645. Bywater T, et al. The Measurement Properties and Acceptability of a New Parent-Infant Bonding Tool (Me and My Baby) for Use in United Kingdom Universal Healthcare Setting: A Psychometric, Cross-Sectional Study. Front Psychol. 2022;14(13):804885. doi:10.3389/fpsyg.2022.804885. Aljaberi et al. Rasch Modelling and Multilevel Confirmatory Factor Analysis for the Usability of The Impact of Event Scale-Revised (IES-R) During the Covid-19 Pandemic. Healthcare (Basel). 2022;10(10):1858. doi:10.3390/healthcare10101858. John M. Linacre. A User's Guide to WINSTEPS®MINISTEP Rasch-Model Computer Programs. 2023. ISBN: 0-941938-03-4. Fallon V, Davies M, Christiansen P, Harrold AJ, Silverio AS. The Postpartum Specific Anxiety Scale: Confirmatory Factor Analyses and Relationships with Birth Experience. Archives of Women's Mental Health. 2022;25:655-65. https://doi.org/10.1007/s00737-022-01233-9. Nielsen MG, et al. The Construct Validity of The Perceived Stress Scale. J Psychosom Res. 2016;84:22-30. doi:10.1016/j.jpsychores.2016.03.009. Allison C, Baron-Cohen S, Stone MH, Muncer SJ. Rasch Modelling and Confirmatory Factor Analysis of The Systemizing Quotient-Revised (SQ-R) Scale. Span J Psychol. 2015;30(18):E16. doi:10.1017/sjp.2015.19. Lee DG, Sohn H, Bae BH, Song Y. Validity of the Breakup Strategies Questionnaire in Korea: Exploratory Structural Equation Modeling and Rasch's Modeling. Psychol Rep. 2018;121(1):163-183. doi:10.1177/0033294117720936. Kurnianto A, Sunjaya KD, Rinawan RF, Hilmanto D. Validation and Reliability of Lifestyle Instruments for Indonesian Adolescents with Hypertension Family History: A Rasch Model. Macedonian Journal of Medical Sciences. 2023;11(B):109-14. https://doi.org/10.3889/oamjms.2023.11127. Silverio Sergio A, et al. A Validation of the Postpartum Specific Anxiety Scale 12 Item Research Short-Form for Use During Global Crises with Five Translations. BMC Pregnancy and Childbirth. 2021;21:112. https://doi.org/10.1186/s12884-021-03597-9. Wijayanto F, Bucur IG, Mul K, Groot P, Van Engelen BGM, Heskes T. Semi-Automated Rasch Analysis with Differential Item Functioning. Behav Res Methods. 2022. doi:10.3758/s13428-022-01947-9. Gondodiputro S, Wiwaha G, Lionthina M, Sunjaya KD. Reliability and Validity of the Indonesian Version of the World Health Organization Quality of Life-Old (WHOQOL-OLD): A Rasch Modeling. Medical Journal of Indonesia. 2021;30(2):143-51. https://doi.org/10.13181/mji.oa.215065. Hilfi Lukman, et al. Rasch Model Analysis of the Indonesian Version of the World Health Organization Disability Assessment Schedule (WHODAS 2.0). The Kitakanto Medical Journal. 2021;71:275-88. doi:10.2974/kmj.71.275. Packham T, MacDermid JC, Selles RW, Slijper HP, Wouters R. Rasch Analysis of the Michigan Hand Questionnaire. Value Health. 2022;25(4):638-646. doi:10.1016/j.jval.2021.09.015. Amiri SM, et al. Psychometric Evaluation of the Postpartum Specific Anxiety Scale-Research Short-Form Among Iranian Women (PSAS-IR-RSF). BMC Pregnancy and Childbirth. 2023;23:531. https://doi.org/10.1186/s12884-023-05855-4. Slomian J, Honvo G, Emonts P, Reginster JY, Bruyere O. Consequences of Maternal Postpartum Depression: A Systematic Review of Maternal and Infant Outcomes. Women's Health. 2019;15:1-55. doi:10.1177/1745506519844044. Davies SM, Christiansen P, Harrold AJ, Silverio SA, Fallon V. Creation and Validation of the Postpartum Specific Anxiety Scale (PSAS). Arch Womens Ment Health. 2021;24(6):957-69. Okunola TO, Awoleke JO, Olofinbiyi B, Rosiji B, Omoya S, Olubiyi AO. Postnatal Blues: A Mirage or Reality. J Affect Disord Reports. 2021;6:100237. Available from: https://doi.org/10.1016/j.jadr.2021.100237. Wulandari RP, Mufdlilah M. Demographic and Obstetric Factors Influencing Postpartum Quality of Life. Journal Obstetrics. 2020;9(2):129.